Adsorption/ Regeneration Coupling Process Using Ozone on Cobalt Supported on Activated Carbon for Nitrobenzene Degradation. (2nd January 2021) - Abdedayem, Asma; Guiza, Monia; Ouederni, Abdelmottaleb
ABSTRACT: This study investigates the removal of a model pollutant, nitrobenzene (NB), from water by combining adsorption onto a new catalyst cobalt supported on activated carbon (Co/AC) and regeneration with ozone. The adsorption equilibrium isotherms of NB onto the raw activated carbon (AC) and the new catalyst enabled the effect of cobalt on the adsorption capacity of the raw carbon. The Nitrobenzene adsorption mechanism on both AC and Co/AC was discussed based on the experimental data. Equilibrium parameters were calculated and correlated with the adsorption behaviors using different models. Results indicate that the Freundlich model best describes the experimental data. The intra-particle diffuse, external diffuse, pseudo-first-order and pseudo-second-order kinetic models were applied to test the experimental data. The pseudo-second order exhibited the best fit for the kinetic studies. Sequential process coupling adsorption and oxidation by ozone was evaluated on the different studied materials. The obtained results assert that, with the combined ability of ozone oxidant and the prepared catalyst/adsorbents, there is an important possibility of total removal of pollutants and restore the initial adsorption capacity of both used materials. The degradation mechanism of the AD/regeneration process on AC and Co/AC was proposed. Several analytical techniques were employed to evaluate the effect of ozone on the adsorbent surface characteristics such as Nitrogen adsorption-desorption at 77 K, XPS and SEM.